The Role of Virtues in the Framing of Decisions - Bastons, Miquel (Journal of business ethics, 2008)
This article explores links between the modern theory of rational choice and ethics. Ethics allows us to answer an unsolved question in modern decision theory: the structuring problem in decisions. Such a problem cannot be solved coming from the principle of expected utility. This principle can solve the problem of ‚choosing’ among given alternatives, but does not establish which alternatives should be taken into account in decision. In order to understand the structuring problem, the act of ‚choosing’ has to be completed with three human acts: operating, predicting and evaluating. At the same time, the subjective criteria of rational choice – probability and utility – have to be completed with three objective criteria: efficiency, truth and goodness. Utility is a subjective value of an alternative considered in relation to another. Efficiency, truth and goodness are objective qualities of the joint alternatives in relation to the reality: the real operating possibilities of the agent, the real possibilities of his environment and the true good produced. So, the rule that guarantees a decision to be optimal would be: “do that which most certainly maximises our preferences, according to real operative resources, true knowledge and the right will”. However, this rule cannot be applied without the development of virtues, which could be seen as the main moral competences in decision-making.